A fatal bite from the burrowing asp Atractaspis corpulenta (Hallowell 1854). (August 2016) - Tilbury, Colin R.; Verster, Janette
Abstract: Bites from the various species of Atractaspis are a common occurrence in Africa but deaths are very unusual. Of the 19 described species, the clinical effects of the bite of only seven have been described, and in only three ( Atractaspis irregularis, Atractaspis microlepidota and Atractaspis engaddensis ) have fatalities been documented. A case of envenomation is described following a bite to a finger by Atractaspis corpulenta, which resulted in sudden death approximately two and a half hours later. The victim received antivenom and although anaphylaxis to this cannot be ruled out, we consider it to be unlikely to be the cause of death. A late autopsy was performed and the findings and their interpretation are discussed. The previous case fatalities, toxic fractions and clinical effects of Atractaspis venom are briefly reviewed. Highlights: The first fatality following the bite of Atractaspis corpulenta is described. The precise mechanism of death was unclear from the clinical record. Autopsy findings were largely non-specific – could not exclude anaphylaxis. Clinical effects and mode of action of Atractaspis venoms are briefly reviewed.